BOOK REVIEWS (Journal of Finance, 1960)
Book reviewed in this article: Business Finance: Organizing and Financing Business . By J oseph H. B onneville , L loyd E. D ewey , and H arry M. K elly . Corporation Finance . By F loyd F. B urtchett and C lifford M. H icks , with the assistance of K. L. B roman . Financial Organization and Management of Business . By C harles W. G erstenberg . Corporation Finance . By R ichards C. O sborn . Jim Fisk: The Career of an Improbable Rascal . By W. A. S wanberg . Insurance: Insurance: Principles and Practices . By F rank J oseph A ngell . Health Insurance . By O. D. D ickerson . Price Discrimination in Property and Liability Insurance . By C. A rthur W illiams , J r . Foreign Trade and Finance . Edited by W illiam R. A llen and C lark L ee A llen . Balance of Payments and Economic Growth . By J. M. L etiche . Investments: Making Money in Today's Market . By R alph C. E pstein . Investment Management . By H arry C. S auvain . Investment in Producing Oil Royalties . By C arl S. W ebber and W alter S. S achs , J r . Money and Banking: Business Loans of American Commercial Banks . Edited by B enjamin H aggott B eckhart . The Bank That Banks Built: The Story of Savings Banks Trust Company, 1933–1958 . By A dolf A. B erle , J r . Economic Fluctuations: Growth and Stablity . By M aurice W. L ee . Business Conditions Analysis . By J ohn P. L ewis . A General Theory of the Price Level, Output, Income Distribution, and Economic Growth . By S idney W eintraub . Public Finance: Government Finance: An Economic Analysis . By J ohn F. D ue . Federal Budget and Fiscal Policy, 1789–1958 . By L ewis H. K immel . Public Finance . Edited by R ichard W. L indholm . The Theory of Public Finance: A Study in Public Economy . By R ichard A. M usgrave . Readings in the Economics of Taxation . Edited by R ichard A. M usgrave and C arl S. S houp . Taxation of Agricultural Lands in Underdeveloped Economies . By H askell P. W ald .